Effects of yoga on stress in stressed adults: a systematic review and meta-analysis - Schleinzer, Alina; Moosburner, Alina; Anheyer, Dennis; Burgahn, Laura; Cramer, Holger (Frontiers in Psychiatry, 2024)
Background With the increasing prevalence of stress, stress reduction is getting more and more important. Yoga is being considered as a non-pharmacological treatment option for stress. Objective Investigation of the effects of yoga on stress in stressed adults from the general population. Methods Databases were searched up to March 17, 2023 (updated search on May 17, 2024). Randomised controlled trials (RCTs) of yoga for stressed adults were included if they assessed perceived stress. Further outcomes were quality of life and stress-related physiological measures. Standardised mean differences (SMDs) and 95% confidence intervals (CIs) were calculated. The quality of the included studies was assessed using the Cochrane tool, and the quality of the evidence for each outcome was graded according to the GRADE recommendations. Results A total of 13 RCTs with 1026 participants were included in the qualitative analysis and nine RCTs in the quantitative analysis. The meta-analyses revealed low quality of evidence for short-term effects of yoga on stress compared to passive control groups (SMD=-0.69, 95%CI=-1.12- -0.25) and low quality of evidence for long-term effects on stress in favour of active control groups (SMD=0.23, 95%CI=0.06-0.40). There was moderate quality of evidence for short-term effects of yoga on quality of life compared to passive control groups (SMD=0.86, 95%CI=0.72-1.00). No adverse events occurred in the three safety reporting studies. Conclusions As there is low quality of evidence for short-term effects of yoga on perceived stress in stressed adults from the general population compared to passive control groups, yoga can be considered as a non-pharmacological treatment option for stress reduction. Systematic review registration https://inplasy.com/wp-content/uploads/2023/03/INPLASY-Protocol-4595.pdf INPLASY, identifier 202330062.